L’occupation britannique de Chypre et la Cyprus Police (1878-1914) - Patrick Louvier (Revue des Mondes Musulmans et de la Méditerranée)
The Anglo-Turkish Convention of 4 June 1878 was drafted after the Russo-Turkish War of 1877-1878 and granted control of Cyprus to Great Britain. In need of a multipurpose tool for law enforcement, the government established an ad hoc semi military force (the Cyprus Police), whose origins are part of the history of the gendarmeries (military police forces), created at that time in the British and Ottoman empires. Initially recruited among Ottoman indigenous forces, the insular police was predominantly Muslim until 1914 for pragmatic yet increasingly ideological reasons. While the Cyprus Police was quickly recognized for its competence, the rise of enosism after 1890 tarnished its impartiality. The communitarisation of debates concerning its management as well as the fear of excesses led to the overrepresentation of Muslims in the Cyprus Police whose self-control during clashes in the Turco-Italian war (1911-1912), confirmed its management’s competence and awareness of the realities in Cyprus.